Penggunaan Bahasa Indonesia Dalam Pelatihan Dan Intruksi Olahraga - Muhamad Rifki; Safa Maida Arlis; Naufal Taufikul Hakim Azhar; Dinda Lupita Saiful Anggraini; Robby Bahari; Mochamad Whilky Rizkyanfi (Departement of Mathematics Education, 2024)
The research aims to analyze the use of the Indonesian language in the context of sports training and instruction. This study utilizes a qualitative approach with data collection techniques including participatory observation, interviews with coaches, and analysis of relevant documents on sports training and instruction. The main findings indicate that the use of the Indonesian language in sports training and instruction has a significant impact on athletes' understanding, safety, and performance